2009
DOI: 10.1242/jeb.025957
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional classification of ion-absorbing mitochondria-rich cells in the gills of Mozambique tilapia

Abstract: SUMMARY To clarify ion-absorbing functions and molecular mechanisms of mitochondria-rich (MR) cells, Mozambique tilapia (Oreochromis mossambicus) were acclimated to artificial freshwaters with normal or lowered Na+ and/or Cl– concentration: (1) normal Na+/normal Cl– (control); (2) normal Na+/low Cl–; (3) low Na+/normal Cl–; and (4) low Na+/low Cl–. Scanning electron microscopy (SEM) revealed that concave and convex apical surfaces of MR cells predominantly developed in low Na+ and low Cl– waters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 42 publications
7
71
1
Order By: Relevance
“…Quantitative expression data from teleosts suggests that NHEs may play a key ion regulatory role in some FW-acclimated fish species. NHE3 mRNA was significantly upregulated in the gills of Mozambique tilapia, Oreochromis mossambicus, and zebrafish, Danio rerio, acclimated to low-Na + waters (Yan et al, 2007;Inokuchi et al, 2009), whereas NHE2 expression increased in the gills of killifish, Fundulus heteroclitus, also when exposed to FW (Scott et al, 2005). Further evidence that NHEs perform Na + uptake was provided by Esaki et al (Esaki et al, 2007), who showed that Na + influx across MRCs of zebrafish larvae was severely reduced upon application of a selective NHE inhibitor, EIPA.…”
Section: Plasma Osmolality Urea and Electrolytesmentioning
confidence: 99%
“…Quantitative expression data from teleosts suggests that NHEs may play a key ion regulatory role in some FW-acclimated fish species. NHE3 mRNA was significantly upregulated in the gills of Mozambique tilapia, Oreochromis mossambicus, and zebrafish, Danio rerio, acclimated to low-Na + waters (Yan et al, 2007;Inokuchi et al, 2009), whereas NHE2 expression increased in the gills of killifish, Fundulus heteroclitus, also when exposed to FW (Scott et al, 2005). Further evidence that NHEs perform Na + uptake was provided by Esaki et al (Esaki et al, 2007), who showed that Na + influx across MRCs of zebrafish larvae was severely reduced upon application of a selective NHE inhibitor, EIPA.…”
Section: Plasma Osmolality Urea and Electrolytesmentioning
confidence: 99%
“…Anion exchanger that takes up Cl Ϫ in exchange of other anion is also unlikely as it functions without Na ϩ in media (27). Recently, NCC was identified on the apical side of the gill cells and was suggested to be responsible for Na ϩ and Cl Ϫ uptake in zebrafish and tilapia in FW (11,12). Consistent with the results of zebrafish and tilapia, transfer of FW eels to 150 mM NaCl solution containing HCTZ, a potent NCC blocker, significantly inhibited Slc26a6a gene expression in the kidney compared with controls.…”
Section: Ncc Responsible For CL ϫ Uptake From the Environmentmentioning
confidence: 99%
“…For freshwater fish gills, pharmacological and molecular evidence for the involvement of Cl -/HCO 3 -exchange in Cl -uptake has recently been provided Bayaa et al, 2009). The potential role of cation-chloride co-transporters has also been shown (Inokuchi et al, 2009;Inokuchi et al, 2008;Horng et al, 2009). In both mechanisms, the exact driving force for Cl -uptake is still unknown.…”
Section: CLmentioning
confidence: 99%